Cerebral revascularization through the external carotid arteries: Venous graft from the subclavian to the external carotid - Palma, Eduardo; Rodríguez Martínez, Ricardo; Berois, Néstor; González Vales, Horacio; Arias, José; Pérez Lagrave, A.; Soncini, J A (Cirugía del Uruguay, 1973)
A case of ateromatous obstruction of both internal carotids was successfully treated through revascularization of externa! carotids by venous graft from subclavian on one side and thromboendarteriectomy on the other.